Social Licensing and the Extractive Industry - Flórez Peña , Carmen Graciela; Díaz Gamboa, Luis Bernardo; López Solano, Cristian Alexis (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The purpose of this article is to make an approximation to the concept of social licensing; a figure that emerges from the multiple efforts of jurisprudence to agree on the economic interests of extractive companies and the collective fundamental rights of the inhabitants who reside in the jurisdiction of the municipality where a mining, oil or energy project is to be carried out.